Implementation of Foreign Direct Investment (FDI) in Agricultural Retail Sector in India: An Economists’ Opinion - Mukteshawar, Rati; Shehrawat, P S; Malik, J S; Godara, A K (Indian Journal of Extension Education, 2020)
Agricultural retail sector is one of the most important pillars of Indian economy and it is growing at a phenomenalÂ pace. FDI in agricultural sector plays an integral role in the country’s economic growth. The aim of research paper is to explore the opinion of agricultural economists towards FDI in agricultural retail sector. The studyÂ was conducted in Haryana State. The study revealed that FDI will promote well â€“ organized retail stores withÂ minimum staffâ€™ was found highly prospective which got highest mean score of 2.67. Major advantages of FDI found were ; FDI may bring growth and prosperity in agricultural retail sector (mean score 2.65), FDI may improve infrastructure facilities (mean score 2.58), Inflow of foreign capital may increase after the implementation of FDI (mean score 2.58), FDI may provide high quality of farm inputs (mean score 2.53). Small and marginalÂ farmers may suffer (mean score 2.47), Increases the real estate prices (mean score 2.33) and Discourage local retailers (mean score 2.32), No real benefit to famers and FDI may uproot the domestic retail stores with weight mean score 2.25 were major disadvantages of FDI.